Past, Present and Future Trends in Cotton Breeding - Zafar, Yusuf (IntechOpen, 2018)
Cotton, a source of natural fiber for textile industry, has a long breeding history aiming at increasing cotton fiber yield and its quality. Newly developed cotton varieties poorly respond in low-input environments. Secondly, the impact of changing climate may threaten the cotton production in the future. To address these challenges, efforts toward the development of resilient cotton varieties have been initiated using genetic and modern genomic approaches. In this book, research updates on cotton fiber types and properties, DNA markers for selecting desirable cotton plants, and cotton fiber genomics were compiled. Also, the modern breeding trends including development of transgenic cotton and the biosafety studies and possibilities of improving cotton genome using modern genome editing tools were also compressively discussed.